THE INCREASING THE DURATION OF FUNCTIONAL BEVERAGES METHODS - Marina V. Gernet; I. N. Gribkova; O. A. Borisenko (Пищевые системы)
In the Russia beverage market, functional beverages are increasingly popular with the population due to their intensive lifestyle and worsening environmental situation. Of great importance is the shelf life of drinks, since they determine the presence in the composition of useful nutrients that affect the various systems of functioning of the human body. The main groups of functional compounds are given. Ways to increase the shelf life of beverages, all aspects and their impact on the safety of the functional components of beverages are considered. The role of flavonoids as one of the groups of functional compounds has been evaluated. Recent studies on the effect of certain functional compounds on each other are given.